Research Progress of Liquid Biopsy Based on DNA Methylation in Tumor Diagnosis and Treatment - Yunxia Bao; Xianzhao Wang; Bingjie Zeng; Yichun Shi; Yiman Huang; Yiwen Huang; Shuang Shang; Liang Shan; Lifang Ma (Biomolecules)
Liquid biopsy has been gradually applied to the clinical diagnosis and treatment of tumors because of its non-invasive and real-time reflection of the tumor status, as well as the convenience of sample collection, which allows the detection of primary or metastatic malignant tumors and reflects the heterogeneity of the tumors. DNA methylation, which is a type of epigenetic modification, is essential in the progression of tumors. This review introduces the common DNA methylation analysis methods and discusses their advantages and disadvantages, focusing on the new progress of DNA methylation-based liquid biopsy in tumor diagnosis and treatment.